2015
DOI: 10.1208/s12248-015-9782-0
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Immunogenicity of rHuPH20, a Hyaluronidase Enabling Subcutaneous Drug Administration

Abstract: Recombinant human PH20 hyaluronidase (rHuPH20) is used to facilitate dispersion of subcutaneously delivered fluids and drugs. This report summarizes rHuPH20 immunogenicity findings from clinical trials where rHuPH20 was co-administered with SC human immunoglobulin, trastuzumab, rituximab, or insulin. Plasma samples were obtained from evaluable subjects participating in ten different clinical trials as well as from healthy plasma donors. A bridging immunoassay and a modified hyaluronidase activity assay were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 46 publications
5
45
0
1
Order By: Relevance
“…Three of 24 pediatric patients (aged 13, 14 and 17 years) developed transient anti-rHuPH20 titers (≥1:160) that decreased over time with continued IGHy treatment [44]. Isotyping of anti-rHuPH20 antibodies showed similar ratios of IgM, IgA and IgG (isotypes IgG1, IgG2, IgG3 and IgG4) for treatment-emergent antibodies from patients in the Phase III study, compared with rHuPH20 antibodies in a baseline-positive population with pre-existing rHuPH20 antibodies ( Figure 5) [26]. Cross-reactivity immunoassays of anti-rHuPH20 antibodies and endogenous PH20 (e.g., human sperm-derived hyaluronidase) showed that IGHy does not cross-react with PH20 analogs.…”
Section: Anti-ph20 Immunogenic Responsementioning
confidence: 94%
See 4 more Smart Citations
“…Three of 24 pediatric patients (aged 13, 14 and 17 years) developed transient anti-rHuPH20 titers (≥1:160) that decreased over time with continued IGHy treatment [44]. Isotyping of anti-rHuPH20 antibodies showed similar ratios of IgM, IgA and IgG (isotypes IgG1, IgG2, IgG3 and IgG4) for treatment-emergent antibodies from patients in the Phase III study, compared with rHuPH20 antibodies in a baseline-positive population with pre-existing rHuPH20 antibodies ( Figure 5) [26]. Cross-reactivity immunoassays of anti-rHuPH20 antibodies and endogenous PH20 (e.g., human sperm-derived hyaluronidase) showed that IGHy does not cross-react with PH20 analogs.…”
Section: Anti-ph20 Immunogenic Responsementioning
confidence: 94%
“…An additional 2 patients developed a 1:160 titer during the extension study, for an overall rate of 18% (15 of 83 patients). Longitudinal data from 5 patients with titers >1:160 demonstrated that titers decreased over time despite continued exposure to IGHy (Figure 4) [26,39]. Three of 24 pediatric patients (aged 13, 14 and 17 years) developed transient anti-rHuPH20 titers (≥1:160) that decreased over time with continued IGHy treatment [44].…”
Section: Anti-ph20 Immunogenic Responsementioning
confidence: 98%
See 3 more Smart Citations